2004
DOI: 10.1291/hypres.27.731
|View full text |Cite
|
Sign up to set email alerts
|

Green Coffee Bean Extract Improves Human Vasoreactivity

Abstract: Our previous study revealed the antihypertensive effects of green coffee bean extract (GCE) ingestion in spontaneously hypertensive rats. We suggested that this antihypertensive action was due to the fact that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 34 publications
(26 reference statements)
4
89
1
2
Order By: Relevance
“…Another study in humans also indicated that consumption of a green coffee bean extract (main component: chlorogenic acids) enhances vascular endothelial function. 25 These results indicate that ingestion of HHQ-reduced coffee decreased blood pressure in subjects with mild hypertension. The decreased blood pressure was associated with reduced ROS and improved vascular endothelial function.…”
Section: Discussionmentioning
confidence: 79%
“…Another study in humans also indicated that consumption of a green coffee bean extract (main component: chlorogenic acids) enhances vascular endothelial function. 25 These results indicate that ingestion of HHQ-reduced coffee decreased blood pressure in subjects with mild hypertension. The decreased blood pressure was associated with reduced ROS and improved vascular endothelial function.…”
Section: Discussionmentioning
confidence: 79%
“…[11][12][13] Of great interest, investigations during the last decade have demonstrated that the consumption of green coffee extracts produces an anti-hypertensive effect in both rats and humans, 14,15 as a result of improved endothelial or vascular function. 16,17 Such biological effects have been attributed to the presence of CGAs in green coffee. The purpose of this invited review is to highlight the findings pertinent to the effects and mechanisms of CGA on arterial blood pressure control and to discuss unanswered questions that warrant further research effort.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, green coffee bean extract (the main component of which is chlorogenic acids) improved vascular endothelial function. 26) These findings suggest that HHQ-reduced coffee decreases blood pressure by improving vascular endothelial function. In the present study, more than 80% of the subjects were treated with either an ACEI or ARB.…”
Section: Discussionmentioning
confidence: 91%